ImmunoglobuliN in the Treatment of Encephalitis (IgNiTE): protocol for a multicentre randomised controlled trial - R Kneen; M Lim; A Vincent; A J Pollard; W K Chong; L-M Yu; M A Iro; M Sadarangani; M Absoud; C A Clark; A Easton; V Gray; et al. (BMJ Open)
Introduction Infectious and immune-mediated encephalitides are important but under-recognised causes of morbidity and mortality in childhood, with a 7% death rate and up to 50% morbidity after prolonged follow-up. There is a theoretical basis for ameliorating the immune response with intravenous immunoglobulin (IVIG), which is supported by empirical evidence of a beneficial response following its use in the treatment of viral and autoimmune encephalitis. In immune-mediated encephalitis, IVIG is often used after a delay (by weeks in some cases), while diagnosis is confirmed. Wider use of IVIG in infectious encephalitis and earlier use in immune-mediated encephalitis could improve outcomes for these conditions. We describe the protocol for the first ever randomised control trial of IVIG treatment for children with all-cause encephalitis.Methods and analysis 308 children (6 months to 16 years) with a diagnosis of acute/subacute encephalitis will be recruited in ∼30 UK hospitals and randomised to receive 2 doses (1 g/kg/dose) of either IVIG or matching placebo, in addition to standard treatment. Recruitment will be over a 42-month period and follow-up of each participant will be for 12 months post randomisation. The primary outcome is ‘good recovery’ (score of 2 or lower on the Glasgow Outcome Score Extended—paediatric version), at 12 months after randomisation. Additional secondary neurological measures will be collected at 4–6 weeks after discharge from acute care and at 6 and 12 months after randomisation. Safety, radiological, other autoimmune and tertiary outcomes will also be assessed.Ethics and dissemination This trial has been approved by the UK National Research Ethics committee (South Central—Oxford A; REC 14/SC/1416). Current protocol: V4.0 (10/03/2016). The findings will be presented at national and international meetings and conferences and published in peer-reviewed journals.Trial registration numbers NCT02308982, EudraCT201400299735 and ISRCTN15791925; Pre-results.